ChemInform Abstract: NaTi3FeO8: A Novel Anode Material for Sodium‐Ion Batteries. Issue 32 (August 2015) - Hou, Junke; Niu, Yubin; Yi, Fenglian; Liu, Sangui; Li, Yutao; He, Hong; Xu, Maowen
Abstract NaTi3FeO8 is prepared by calcination of stoichiometric amounts of Na2CO3, Fe2O3, and TiO2 in air (950 °C, 12 h).